An Innovative Solution for Battery Draining in 5G Devices Using Alternate Routing Model. (29th September 2022) - Sivasubramanian, M.; Vignesh, J.; Senthil kumar, V.; Sumathi, S.; Sathish, R.; Parasuraman, Kumar; Kumar, B Santhosh; Kathirvelu, M; Bojaraj, Leena; K, Srihari; Sbhat, Negasi Tsegay
Abstract : When the electrolyte is layered, excessively large and prolonged charging and exhaust currents lead to the random tendency of reactions in different parts of the electrodes. This was leading to mechanical stresses and the warming of the plates of the battery. The presence of nitric and acetic acid contaminants in the electrolyte improves the oxidation of the deeper layers of positive electrodes. Because lead dioxide has a larger volume than lead, electrodes expand and curve. Positive electrodes are subject to war and growth. The negative electrode curve is mainly caused by the nearby distracted positive people. The adjustment of the distracted electrodes can only be carried out by removing the battery. The lack of sulfate and fully charged electrodes are subject to correction because they are soft and easy to adjust. The main contribution of this proposed work is to provide an innovative solution to resolve the battery draining issues in 5G devices with the help of an alternate routing model. The proposed model will provide an idea that is used to slice distracted electrodes washed with water and placed between soft, hard boards. Generally, on the top board, a load is installed, which increases the edges of the electrodes. Electrodes are banned directly or through the amplitude of a top or hammer to avoid the destruction of the active layer; hence, the draining of the battery was reduced.